2018
DOI: 10.1108/intr-03-2017-0116
|View full text |Cite
|
Sign up to set email alerts
|

The impact of uncertain rewards on customers’ recommendation intention in social networks

Abstract: Purpose The purpose of this paper is to research the effect of uncertain rewards on the recommendation intention in referral reward programs (RRPs) and investigate the interaction of tie strength and reward type on the recommendation intention. Design/methodology/approach The research adopts a quantitative exploratory approach through the use of experiments. Study 1 adopted a 2×2 between-participants design ((reward type: certain reward vs uncertain reward)×(tie strength: strong tie vs weak tie)). Respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 123 publications
(162 reference statements)
1
8
0
Order By: Relevance
“…This supports the results of the present study [23]. Thus, reinforcement of reliability, confidence, and empathy in Hapkido has a positive effect on recommendation intention, which means an improvement in satisfaction with service quality and benefits to others [24].…”
Section: Discussionsupporting
confidence: 91%
“…This supports the results of the present study [23]. Thus, reinforcement of reliability, confidence, and empathy in Hapkido has a positive effect on recommendation intention, which means an improvement in satisfaction with service quality and benefits to others [24].…”
Section: Discussionsupporting
confidence: 91%
“…Third, this research found that online tipping is very different from typical spending behavior. For example, PTM tends to be spent on oneself, whereas STM is more likely to be spent on others or impulsive purchases (Liu et al , 2018; Wang et al , 2018). Following this logic would lead to the intuition that STM should result in a higher willingness to engage in online tipping than PTM because online tipping is undertaken for others.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research focused mainly on the effects of reward size and reward scheme on rewarded referral likelihood (e.g., Ryu and Feick, 2007 ; Verlegh et al, 2013 ; Wirtz et al, 2013 , 2019 ; Orsingher and Wirtz, 2018 ). Only a few studies explored reward type (e.g., Jin and Huang, 2014 ; Wang et al, 2018 ; Zhang et al, 2019 ); nevertheless, they emphasize the explicit forms (e.g., monetary vs. in-kind) but overlook the implicit nature (utilitarian or hedonic) of the rewards. Our findings reveal that the effectiveness of utilitarian and hedonic rewards, even with the same explicit form (e.g., both liquid detergent and movie tickets used in Study 2 are in-kind), can be considerably diverse.…”
Section: Discussionmentioning
confidence: 99%
“… Zhang et al (2019) addressed the analogous topic in the specific context of electronic referral and demonstrated the advantage of cinema ticket vouchers (typically hedonic) over cash. In addition, Wang et al (2018) found that uncertain rewards generate a higher referral intention than certain rewards, because the former is with a more positive experience. However, these studies focus almost exclusively on the type of rewards and neglect other factors that may play an important role in consumers’ evaluation toward utilitarian vs. hedonic rewards.…”
Section: Introductionmentioning
confidence: 99%